Gerenciamento dos cuidados de enfermagem em uma comunidade jesuítica da província do brasil meridional (BRM) - Bonicoski, Orival (Universidade do Vale do Rio dos Sinos, 2013)
The present study aimed to the implementation of management of nursing care in the community John Paul II the Province of Southern Brazil (BRM), located in Florianópolis / SC as pilot plan study. Describes the demographic, clinical and health by identifying health needs, streamlining the health care and building a flowchart of clinical accompaniments of this community. Characterized as an intervention study with quantitative approach. It is a community of 13 Jesuits, of varying ages and diverse work activities. The management of nursing actions implemented focuses on the Institute of St. Joseph, Jesuit House Health of BRM in São Leopoldo / RS. The age ranged from 33 to 82 years, on the merits, the majority are descendants of the state of Rio Grande do Sul The members have higher education appears more clearly. Regarding the religious category, had to priests, brothers and scholastics, with diverse occupations, according to the religious category and mission received. The fact that they are owners of the institution, makes the workday is maximum established by law. Another point was researched leisure, this appears among all so varied. Clinical data in relation to Body Mass Index (BMI) and the Mini Nutritional Assessment (MNA), were found jesuits, underweight, risk of malnutrition, undernourished, overweight and obese. Also appeared in the habit of smoking and drinking alcohol. . Few realized the physical activity. Clinical diagnoses that appeared was more hypertension and T2DM. Most have no doctor and do not conduct medical examinations periodically. None of the respondents have the vaccination schedule so complete and updated. The use of support networks in health, looking occurs between health centers, pharmacies, examination center and radiological diagnostics and physiotherapy clinic. Medications are managed by the subjects researched and prescribed according to clinical diagnoses. In self-perception in health assessment was between "good" and "very good", which leads us to believe that everyone has a positive perception of their health. The spirituality of the Jesuits, has shown that there is an intimate relationship between the transcendent and the imminent. According to the health situation of the Jesuits, were listed nursing diagnoses and interventions according to the taxonomy of the International Classification of Nursing Practice in Public Health (CIPESC), allowing a plan of nursing care to the community John Paul II and another individual character. This care plan must be monitored periodically by a nurse, via a flowchart. Other conditions as found, do not perform periodic medical examinations; has no doctor, do not take advantage of support networks, not guidelines on spirituality and the use of medications, are not included with the diagnoses and interventions CIPESC. It is expected, with these interventions, facilitate the development of an instrument for good health management Jesuit Province of the other residences BRM.
Keywords: Religious; Nursing assistance systematization; Prevention; Men's health; Religiosos; Sistematização assistência de enfermagem; Prevenção; Saúde do homem; ACCNPQ::Ciências da Saúde::Enfermagem